2017
DOI: 10.3174/ajnr.a5397
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Characteristics of Ruptured and Unruptured Multiple Aneurysms at Mirror and Ipsilateral Locations

Abstract: Background and Purpose Different hemodynamic patterns have been associated with aneurysm rupture. The objective was to test whether hemodynamic characteristics of the ruptured aneurysm in patients with multiple aneurysms were different from unruptured aneurysms of the same patient. Materials and Methods A total of 24 mirror and 58 ipsilateral multiple aneurysms with one ruptured and the other(s) unruptured were studied. Computational fluid dynamics models were created from 3D angiographies. Case-control stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…These ruptured aneurysms were found to have greater maximal and lower minimal shear stress compared to their unruptured counterparts. 8 The gradient of the WSS has been found to have an effect on cells of the vascular wall, as Dolan et al have demonstrated that a negative WSSG may antagonize the effect of high WSS on gene expression. 10 An additional theory by Meng et al is that both high and low WSS drive aneurysm growth and rupture, with regions of low WSS with high oscillatory shear index undergoing inflammatory cell-mediated destructive remodeling, and regions of high WSS with a positive WSSG undergoing mural cell-mediated remodeling.…”
Section: Wss: An Overviewmentioning
confidence: 99%
“…These ruptured aneurysms were found to have greater maximal and lower minimal shear stress compared to their unruptured counterparts. 8 The gradient of the WSS has been found to have an effect on cells of the vascular wall, as Dolan et al have demonstrated that a negative WSSG may antagonize the effect of high WSS on gene expression. 10 An additional theory by Meng et al is that both high and low WSS drive aneurysm growth and rupture, with regions of low WSS with high oscillatory shear index undergoing inflammatory cell-mediated destructive remodeling, and regions of high WSS with a positive WSSG undergoing mural cell-mediated remodeling.…”
Section: Wss: An Overviewmentioning
confidence: 99%
“…The first set of exclusion criteria were as follows: (a) CFD-unrelated (n = 5), (b) rupture-point-known (n = 10), (c) discriminator-unrelated (n = 26), (d) small number of aneurysms (less than 30) (n = 28), and (e) WSS or OSI undisclosed (n = 11), yielding a total of 32 studies. The second set of exclusion criteria were as follows: (f) location-specific (n = 14), (g) locationundefined (n = 2), (h) size-restricted (n = 1), and (i) metaanalysis (n = 2), yielding a total of 13 studies [38,39,[45][46][47][48][49][50][51][52][53][54][55]. Setting a specific location and size was avoided since those factors are known to be related to the aneurysm rupture rate and may lead to a possible bias; however, casematching studies based on location and size were permitted.…”
Section: Study Selectionmentioning
confidence: 99%
“…From the 13 included studies [38,39,[45][46][47][48][49][50][51][52][53][54][55], the following data were extracted: (1) year of publication, (2) study design, (3) location of aneurysms, (4) number of aneurysms, (5) number of ruptured aneurysms, (6) aneurysmal size, (7) aneurysmal aspect ratio, (8) aneurysmal WSS, (9) aneurysmal normalized WSS (NWSS), (10) aneurysmal OSI, and (11) aneurysmal LSA%. The mean (or median), p value, and area under the curve (AUC) from a receiver operating characteristic (ROC) analysis of these geometric and hemodynamic indexes were extracted.…”
Section: Data Extraction and Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Several morphologic and hemodynamic parameters have been found to differ significantly between ruptured and unruptured aneurysm cohorts in patients with multiple IAs, albeit with conflicting findings. [9][10][11][12][13][14][15] These studies have generally relied on univariate and multivariate regression analyses of pooled data of ruptured and unruptured IAs. Although such methods model the general probability of aneurysm rupture, they are not tailored for identifying which aneurysm ruptured in patients with SAH with multiple aneurysms.…”
mentioning
confidence: 99%